Assessing the world trade organization fit for purpose? : world trade forum - Elsig, Manfred; Hoekman, Bernard M. 1959; Pauwelyn, Joost (Cambridge University Press, 2017)
"With chapters written by scholars who have closely observed the development of the WTO in recent years, this book presents the state of the art in thinking about WTO performance. It also considers important issues such as the origins of the multilateral system, the accession process and the WTO's interaction with other international organisations."--Provided by publisher.